PENGEMBANGAN GAME EDUKASI BAHASA MADURA UNTUK SEKOLAH DASAR MENGGUNAKAN UNITY DENGAN METODE MDLC - Rizqi Azizah Amalia; Walidini Syaihul Huda (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
Local languages are an important part of cultural identity, including the Madurese language. However, its use among elementary school students has been declining, partly due to the lack of engaging and modern learning media. To address this issue, this study developed an Android-based educational game called Maduraku as an interactive medium to introduce the Madurese language to students. The development followed the Multimedia Development Life Cycle (MDLC) method using the Unity platform. Testing results showed that all features functioned properly through black-box testing. Validation from subject matter experts indicated a feasibility score of 80% (categorized as feasible), and user testing revealed a satisfaction rate of 87.5% (categorized as very good). In addition, the game proved effective in improving student learning outcomes, with average scores increasing from 64.4 (pre-test) to 85.4 (post-test), and an N-Gain score of 0.59, classified as moderate improvement. Based on these results, Maduraku is considered effective and suitable as an alternative learning medium to support the preservation and promotion of the Madurese language, especially among elementary school students.